4-H Energy Encounters Workbook - Linda Barber; Marilyn Simmons; Craig R. Miller (EDIS)
Published by the Department of 4-H and Other Youth Programs, University of Florida Cooperative Extension, Institute of Food and Agricultural Sciences, November, 1992. Printed May, 1996; reviewed, June 2002. Reviewed November 2002.